Compromised into marrying the duke - Ashford, Lucy (Harlequin historicals., 2025)
Her first love betrayed her. Now they must marry! Once Anthony had been Marianne's brother's best friend...and the man she'd secretly dreamed of marrying. Then he betrayed her by wedding someone else-for money! Anthony had to bail out his debt-ridden father with his unwanted marriage. Now he's the Duke of Cleveland and back in the ton after his wife's passing. Once he sees captivating Marianne again, an unexpected attraction stirs... When she's upset by a broken engagement, he tries to comfort her-but ends up compromising them both! Is Anthony really willing to have a second convenient marriage, this time to save Marianne's reputation?"--